Mencermati Jendela Matahari di Atas Jakarta sebagai Dasar Perancangan Arsitektur - Tomasowa, Riva (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Over the tropical climate area, the building orientation that is generalized to face North-South needs to be reconsidered. We can solve the issue by thoroughly observe the Solar Windows that is characterised by a certain location on earth. Nowadays, the architects are easily observing their building orientation to the sunusing open sources information. This paper explains those two areas with simulation and modelling strategies from open sources and CAAD. Jakarta as a sample of the observation has it best orientation to face South and East, since those views have shorter radiation time.